The STELVIO trial, a game changer for bronchoscopic lung volume reduction in patients with severe emphysema. Issue 1 (March 2020) - Posthuma, Rein; Vanfleteren, Lowie E.G.W.
Chronic obstructive pulmonary disease (COPD) is characterised by persistent respiratory symptoms and airflow limitation, which is caused by small airway disease (bronchiolitis) and alveolar destruction (emphysema) [1]. Patients primarily suffering from severe emphysema are often limited in exercise capacity due to the consequences of hyperinflation [2]. The STELVIO trial was crucial to ensure that bronchoscopic lung volume reduction using one-way valves has evolved from an experimental intervention into a state-of-the-art treatment option for specific patients with advanced emphysema http://bit.ly/2IgMrsp